Pengaruh Kualitas Produk, Harga, dan Konten TikTok Terhadap Minat Beli Moisturizer Pada Generasi Z - Putri Patricia; Ezra Karamang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The rapid growth of the skincare sector and the widespread use of social media, particularly TikTok, have prompted businesses to understand what drives Generation Z's purchasing intentions. This study aims to examine how product quality, cost, and TikTok content influence purchase intentions for Labore products. This study uses quantitative methods with an explanatory focus. To collect data, an online survey was conducted involving 120 Generation Z participants (17-26 years old) who actively use TikTok and have been exposed to Labore content in urban Indonesia. Multiple linear regression analysis was conducted after validity, reliability, and classical assumptions (normality, multicollinearity, heteroscedasticity) were met. The results show that all three variables have a significant positive effect on purchase intentions (p < 0.05) with product quality as the strongest predictor (β = 0.612; t = 18.117), followed by TikTok content (β = 0.455; t = 14.737) and price (β = 0.092; t = 3.143). The research model explained 91.8% of the variance in purchase intention (R² = 0.918; F = 445.259; p = 0.000). The findings confirm that an integrated strategy combining superior product quality, competitive pricing, and authentic-educational TikTok content can significantly increase Generation Z consumers' purchase intention towards local skincare products.